Teaching Arabic Language To Science Based Students At the International Islamic University Malaysia, Through: Book “Miftah Al-Arabiyyah” - Usop, Mohd Puzhi; Haggag, Hassan (2011)
Designing curriculum is not an easy task. It requires combination of various aspects in order to produce excellent curriculum. The curriculum should encourage high aspirations and ambitions for all. The curriculum should be organized so that they will learn and develop through a variety of contexts within both the classroom and other aspects of school life. If a curriculum is set for certain levels or stages, Each stage should build upon earlier knowledge and achievements. Furthermore, the curriculum should respond to individual needs and support particular aptitudes and talents. It should give each students opportunities for exercising responsible personal choice. This research aims to evaluate the effectiveness of the new designed curriculum to the teaching the Arabic language to science based students at the International Islamic University Malaysia. The book “Miftah Al-Arabiyyah” is considered as an integrated approach for Non- Arabic Speakers. This research was conducted through quantitative and qualitative research. This methodology may grant accuracy in research hypothesis, validity of research assessment, genuine result and comprehensive evaluation. This research started with series of workshops and meetings in order to prepare the text, exercises and activities. Once the preparation of book was completed, The book was then tested to the students. There were 10 lectures and 50 students involved in this process. Questionnaires were distributed to them once they teaching and learning processes were completed within specific time. Findings have shown that the overall result of the new syllabus is moderate. Some of the students prefer the new syllabus while the others do not. We do expect the result and it might be due to some reasons such as time constraints, poor vocabulary, students’ attitude and etc. After getting student’s feedback towards the new book, I would like to provide some recommendations which aim to improve the situation such as adding more language activities, providing more attractive pictures, replacing vague vocabularies and improving the lay out. To sum up, curriculum design is an endless work. Curriculum depends very much on time and environment. Curriculum needs to be refreshed or replaced as time pass by.